2009
DOI: 10.1007/s00787-009-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rumination and distraction on depressed and anxious mood: a prospective examination of the response styles theory in children and adolescents

Abstract: The present study sought to test predictions of the response styles theory in a sample of children and adolescents. More specifically, a ratio approach to response styles was utilized to examine the effects on residual change scores in depression and anxiety. Participants completed a battery of questionnaires including measures of rumination, distraction, depression, and anxiety at baseline (Time 1) and 8-10 weeks follow-up (Time 2). Results showed that the ratio score of rumination and distraction was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 61 publications
(79 reference statements)
5
53
1
3
Order By: Relevance
“…Research has consistently found a gender difference in rumination such that female participants ruminate more than male participants in both adolescent (e.g., Broderick, 1998;Jose & Brown, 2008) and adult (e.g., Butler & Nolen-Hoeksema, 1994;Nolen-Hoeksema, Morrow, & Fredrickson, 1993) samples. Specifically, adolescent research on rumination has shown that higher levels of rumination predict increased depressive symptoms, prospectively (Broderick & Korteland, 2004;Rood, Roelofs, Bogels, Nolen-Hoeksema, & Schouten, 2009;Schwartz & Koenig, 1996;Stone, Hankin, Gibb, & Abela, 2011) and also prolongs depression Roelofs et al, 2009). The same pattern of results holds true for both college (Butler & Nolen-Hoeksema, 1994;Grassia & Gibb, 2008;Nolen-Hoeksema & Morrow, 1991;Nolen-Hoeksema et al, 1993) and adult samples (Nolen-Hoeksema, Larson, & Grayson, 1999).…”
Section: Department Of Psychology Saint Joseph's Universitymentioning
confidence: 69%
“…Research has consistently found a gender difference in rumination such that female participants ruminate more than male participants in both adolescent (e.g., Broderick, 1998;Jose & Brown, 2008) and adult (e.g., Butler & Nolen-Hoeksema, 1994;Nolen-Hoeksema, Morrow, & Fredrickson, 1993) samples. Specifically, adolescent research on rumination has shown that higher levels of rumination predict increased depressive symptoms, prospectively (Broderick & Korteland, 2004;Rood, Roelofs, Bogels, Nolen-Hoeksema, & Schouten, 2009;Schwartz & Koenig, 1996;Stone, Hankin, Gibb, & Abela, 2011) and also prolongs depression Roelofs et al, 2009). The same pattern of results holds true for both college (Butler & Nolen-Hoeksema, 1994;Grassia & Gibb, 2008;Nolen-Hoeksema & Morrow, 1991;Nolen-Hoeksema et al, 1993) and adult samples (Nolen-Hoeksema, Larson, & Grayson, 1999).…”
Section: Department Of Psychology Saint Joseph's Universitymentioning
confidence: 69%
“…For example, in a study of young adolescents, rumination prospectively predicted both depressive and anxiety symptoms (Roelofs et al, 2009). This argument is consistent with a transdiagnostic framework (particularly one used for integrating depression and anxiety) and has the potential to guide treatment efforts aimed at enhancing emotion regulation (e.g., Ellard, Fairholme, Boisseau, Farchione, & Barlow, 2010).…”
Section: Emotion-specific Regulation or General Regulatory Strategies?mentioning
confidence: 97%
“…Rumination and intrusive thoughts are common correlates of both externalizing and internalizing problems, but particularly depression (Wadsworth et al 2005). Rumination has been linked prospectively to depressive and anxious symptoms in children and adolescents (Roelofs et al 2009), and it was found to mediate the relation between female gender and risk for depressive symptoms in low-income, urban, African American youth (Grant et al 2004). Consequently, identification and modification of these involuntary responses may be particularly important components of interventions for at-risk youth (Wadsworth et al 2005).…”
mentioning
confidence: 96%